Imaging of the hamstring muscle complex in elite athletes - Marovic, P.; Koulouris, G. (ASPETAR Sports Medicine Journal, 2016)
Despite most hamstring muscle injuries healing with conservative treatment, the high recurrence rate and often prolonged period out of competition has led to an increase in imaging of this region, particularly in the elite athlete. Both MRI and US have been shown to be effective in assessing the extent of injury, providing a useful guide to the clinician as to the anticipated period of convalescence.